Apparatus and method for analyzing a sample - Markelz, Andrea G; Acbas, Gheorghe; Niessen, Katherine A. (USPTO, 2021)
An apparatus and method for Crystal Anisotropy Terahertz Microscopy (“CATM”) is provided. The apparatus includes an emitter configured to emit a THz pulse and a detector configured to detect the THz pulse after the pulse is transmitted through a sample disposed on a sample surface of the detector. A pulsed radiation generator generates a probe beam to interrogate the detector. The detector may include an electro-optical (“EO”) crystal configured to change in birefringence according to the THz pulse. The sample surface of the detector may have a dielectric coating which is transmissive to THz and reflective to the probe beam. The sample is disposed on the dielectric coating.